TELAAH KONSEP OTAK DALAM AL-QUR’AN: (KAJIAN TAFSIR ‘ILMI TERHADAP KATA AL-NASHIYAH DAN AL-SHADR) - Andi Khuzaimah Tamin (Tanzil: Jurnal Studi Al-Quran, 2022)
The dichotomy between religion and science does not only occur in the west, but also occurs in Islamic civilization after the golden age of Islam during the Abbasid dynasty. which is a place for human thinking. The resulting relationship between the Qur'an and the brain later is the integration relationship of natural theology promoted by Ian Barbour, so that the brain as a microcosm of nature becomes a supporter of experimentation (aqli) from scientific verses of the Qur'an which is the source of naqli. Muslims. Intellect is an important element that distinguishes humans from other creatures. Humans have a brain as a medium for thinking and controlling all their behavior. This study focuses on two terms, namely nāṣiyah and al-ṣadr. Based on the literature review and the deepening of terms that the researchers did, it can be concluded that the brain has an important role in human life. The brain becomes an important place for thinking and becomes the body's control center. The Qur'an uses the terms nāṣiyah and al-ṣadr to explain how big the role and importance of the brain for humans.